PEMAKAIAN MAJAS DALAM RUBRIK GAGASAN PADA SURAT KABAR SOLOPOS DAN IMPLEMENTASINYA DALAM PEMBELAJARAN DI SMP NEGERI 3 SRAGEN - Widianto, Joko; Ngalim, Abdul; Wahyudi, Agus Budi (Jurnal Penelitian Humaniora, 2013)
The objectives of the current study are to describe: (1) types of figurative speech used in ?opinion Rubric? in Solopos newspaper; (2) the compatibility of this figurative speech with the standard competence and the basic competence of Indonesian Language curriculum; and (3) the pedagogical implication of the findings in teaching and learning figure of speech. The object of study is figure of speech used ?Opinion Rubric? of Solopos newspaper. Data collection technique used is documentation and data analysis tech nique used is ?padan subjenis referensial? method. The results are as follows: (1) there are nine types of figurative speech, namely: repetition, equations or simile, hyperbole, metaphor, personification, irony, sarcasm, and synesthesia. The most dominant one is personification; (2) the figurative speech used in this newspaper is compatible with the competence standard and basic competence in Indonesian language curriculum; (3) the students? achievement improve as shown in the increasing score from 62 to 76.